ACSL4 at the helm of the lipid peroxidation ship: a deep-sea exploration towards ferroptosis - Jiang, Yulang; Zhang, Meng; Sun, Mingyu (Frontiers in Pharmacology, 2025)
Lipid peroxidation stands as a prominent hallmark and a prerequisite for the onset of ferroptosis. Lipid metabolism holds a pivotal role in regulating this process, forming the metabolic foundation for cellular sensitivity to ferroptosis. Studies in lipid metabolomics reveal that the activation of Polyunsaturated fatty acids (PUFA), specifically arachidonic acid and adrenoic acid (AdA), mediated by acyl-CoA synthetase long-chain family member 4 (ACSL4), represents a critical step in generating lipid peroxidation substrates. The expression level or enzymatic activity of ACSL4 emerges as a potential indicator of cellular susceptibility to ferroptosis. Additionally, other members of the ACSL family can indirectly influence the occurrence of ferroptosis by modifying the fatty acid composition of the cell membrane. Given the high expression of ACSL4 in various human tumors, targeting lipid peroxidation with ACSL4 as the focal point may pave a new path in tumor therapy. This article provides a brief overview of the primary structure and function of ACSL4, its role in lipid peroxidation, and summarizes the current advancements in drug development targeting ACSL4 and lipid peroxidation.